Introduced oxygen vacancies in cadmium ferrite anode materials via Zn2+ incorporation for high performance lithium-ion batteries. (1st June 2022) - Sanad, Moustafa M.S.; Azab, A.A.; Taha, T.A.
Abstract: Cationic substitution strategy was recognized as an effective approach to create a defective structure and increase the oxygen vacancies in the crystal structure for improving the electrochemical performance of Li-ion batteries components. In this study, Znx Cd1-x Fe2 O4 nanoparticles were synthesized via a facile inexpensive process at low temperature. The collected XRD data confirmed the formation of cubic structure with Fd3m space group. HR-TEM investigations showed the size enlargement of spherical-like crystals with increasing the concentration of doping Zn 2+ ion. FESEM and BET measurements indicated the conversion of micropores in pure CdFe2 O4 into mesopores and macropores in Zn-doped CdFe2 O4 samples. XPS results of O1s spectra elucidated that Zn-doped CdFe2 O4 samples have higher conductivity due to the created lattice defects and oxygen species. Zn-doped CdFe2 O4 anodes exhibit great improvement in their initial discharge capacities ∼1618 and 1880 mAhg −1 upon substitution of Cd with 5% and 10% Zn, respectively. Furthermore, 10% Zn-doped CdFe2 O4 anode displayed the highest Li-ions diffusion coefficient and exchange current density due to the enhanced Li + ions mobility. The increase in zinc content (0.0–0.1) led to a decrease in the DC activation energy from 0.11 to 0.09 eV. Highlights: Nanospheres of cubic crystals observed for CdFe2 O4 & Zn-doped CdFe2 O4 . The higher conductivity for Zn-doped CdFe2 O4 was confirmed from O1s XPS spectra. 10% Zn-doped CdFe2 O4 exhibits the maximum initial discharge capacity∼1880 mAhg −1 . Excellent cyclability due to enhanced Li + mobility and more oxygen vacancies.